A new single‐phase cascaded multilevel inverter topology with reduced number of switches and voltage stress. (15th September 2019) - Siddique, Marif Daula; Mekhilef, Saad; Shah, Noraisyah Mohamed; Sarwar, Adil; Memon, Mudasir Ahmed
Summary: Multilevel inverters have been the vital component for the power electronic systems and have been researched extensively to further enhance their performances in terms of topology and their control. In this paper, a new bidirectional single‐phase multilevel inverter module has been proposed with a reduced number of switches along with lower voltage stresses. The proposed module generates 17 levels at the output with 10 unidirectional switches along with four dc voltage sources with two varieties of dc voltage sources. Moreover, for a higher number of levels, the cascade connection of several modules has been discussed in this paper with three different methods for the selection of dc voltage sources. The proposed module has been compared with several similar topologies, which set the benchmark of the proposed one. The operation and performance of the proposed module have been validated through several simulation and experimental results with different types of load considering a change of modulation index.